2003
DOI: 10.1055/s-2003-39136
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Cartilage in Revision Rhinoplasty

Abstract: Revision rhinoplasty is a challenge in reconstruction to the rhinoplasty surgeon, both in the techniques of repair and the choice of implant material for augmentation grafting. Often, patients seeking revision or reconstructive rhinoplasty have previously undergone septoplasty with sacrifice of major amounts of septal cartilage. These situations confront the surgeon with the need for a decision about the material that will be used for structural grafting. The senior author follows the time-tested approach of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…However, a significant proportion of patients do not self-traumatize the anesthetic area of their face and therefore self-mani- incision was used for reconstruction as the skin was atrophic due to nerve dysfunction (19)(20)(21) .…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant proportion of patients do not self-traumatize the anesthetic area of their face and therefore self-mani- incision was used for reconstruction as the skin was atrophic due to nerve dysfunction (19)(20)(21) .…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study, Endo et al (1991) used auricular cartilage layers as dorsal grafts and reported occasional graft resorption in 1263 patients that had been followed-up for a mean of 8 months. Although they did not mention the amount of resorption, Becker et al (2003) advocated the use of auricular cartilage in revision rhinoplasty, based on their clinical experience. Murrell (2004) has reviewed 101 patients in whom auricular cartilage grafts had been used and reported no graft resorption or extrusion after a follow up of up to 72 months.…”
Section: Discussionmentioning
confidence: 99%
“…13,21 Like septal cartilage, conchal grafts can be used as a single-layered implant or sutured together to increase girth and rigidity. 21,22 In the setting of a thin S-STE, including a portion of soft tissue on the posterior surface of the graft can provide some additional camouflage. 22 Even morselized, though, it occasionally causes palpable and visible dorsal irregularities, due to its intrinsic memory and possibility for resorption.…”
Section: Septal Cartilagementioning
confidence: 99%
“…21,22 In the setting of a thin S-STE, including a portion of soft tissue on the posterior surface of the graft can provide some additional camouflage. 22 Even morselized, though, it occasionally causes palpable and visible dorsal irregularities, due to its intrinsic memory and possibility for resorption. 1 Additionally, conchal cartilage is more curved and less rigid than is septal cartilage; structure and support, therefore, are better achieved with septal or costal cartilage.…”
Section: Septal Cartilagementioning
confidence: 99%